Ambassador’s Mission of the Siberian Cossack Fyodor Skibin to the Kazakh Horde in 1694–1696 - Ivan Kamenetskii (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения)
Introduction. The article provides a survey of the Tobolsk Cossack Fyodor Skibin’s ambassadorial activity to the Kazakh Horde (Kazakh Khanate) in 1694–1696. Methods and materials. The basis of the study is published materials on the history of Russian-Kazakh relations in the 17th century and archival sources from the fund of the Siberian Prikaz of the Russian State Archive of Ancient Acts. Analysis. It is shown that the founder of the large Siberian Skibin dynasty was the ataman of the Zaporozhye Cossacks, Mikhail Skiba (Skibin), exiled to Siberia. The participation of his descendants in ambassadorial missions to the rulers of the eastern states bordering Siberia is considered. The focus is on the motives, circumstances, and results of F. Skibin’s embassy to the Kazakh ruler Tauke-Khan and the forced journey of the Russian ambassadors to Bukhara and Khiva. Previous researchers V.Y. Basin and E.A. Knyazhetskaya have not considered these issues in detail. It was found out that prior to travelling to the Cossack Horde; Skibin had participated in military expeditions to the Kirghiz land and Eastern Transbaikalia (Dauria), where he gained the necessary experience of dealing with Eastern peoples. His journey to and from the ruler of the Kazakhs, Tauke, was fraught with many difficulties and trials. When meeting with Tauke, Skibin defended the interests of the Russian side, seeking the release of detained ambassadors in Turkestan and the liberation of Russian prisoners from bondage. Having overcome various obstacles, Skibin and his companions managed to return to Tobolsk by a roundabout route through Bukhara, Khiva, and Kalmyk possessions. Results. It is established that thanks to their journey, valuable information was obtained about the nature of the Kazakh steppe, the system of government, economic life, and social structure of Kazakhs and residents of Central Asian cities. Skibin’s mission to the Kazakh Khanate, despite failing to achieve its goals, is seen as another step by the Russian government towards establishing permanent ambassadorial ties and peaceful, mutually beneficial relations with the rulers of the eastern states.